The king who loves sex: the function of literature in traditional Malay poetry - Hamdan, Rahimah (International Association of Computer Science and Information Technology Press (IACSIT), 2015)
For the traditional Malay society, it is taboo to talk openly about sexuality. This is due to the perception that literary works that incorporate elements of sexuality will be criticised as weak and inferior work coming from an author with bad morals and character. Furthermore, the traditional Malay authors wrote at the request of the king. Hence, all that was written had to exalt the status of the king as the sovereign ruler. The works should be rich in 'character', so as to consolidate the integration of intellectual, epistemological and cultural values for the moral benefit of the community. However, in examining the literary genre of Hikayat such as Syair Seratus Siti, it has been found that these works include so many elements of sexuality that they indirectly reflect a gender system that was supported by the society. Using Braginsky’s (2001) perspective about the function of literature, this study will weave together two literary functions for entertainment and instruction at the same time. This means that elements of 'sexuality' (entertainment) must be synthesized with teaching functions for the benefit of the audience. The results show that Syair Seratus Siti successfully exploited those functions to the extent that they submerged the elements of sexuality that were reflected by the author from the start.